Pelaksanaan Sistem Pemerintahan Presidensial Dengan Multi Partai Di Indonesia - Suparto Suparto (Faculty of Law, Universitas Pattimura, 2021)
The government system in post-reform Indonesia is a presidential system with many parties. The advantage of this system is that it is more democratic because many parties are considered to accommodate the wishes and interests of people from various backgrounds through political parties, while the weakness is that it is difficult for the ruling party if it is not in the majority. The purpose of this study was to determine the implementation of a presidential system of multi-party governance in post-reform Indonesia. The results of the study are that in a presidential government system with many parties (multi-party system) such as in Indonesia, it will cause problems if no political party wins the election with a majority vote, the President must build a coalition with a number of political parties that have representatives in the House of Representatives (DPR). DPR). Since the holding of the 1999 and 2004 elections, there have been efforts to simplify political parties, by reducing the number of election participants through the electoral threshold and then changing since 2009 to reducing the number of political parties that may sit in parliament by using the minimum threshold requirement (parliamentary threshold). However, this method has not been successful because there are still relatively many political parties sitting in parliament, this is due to the parliamentary threshold that is too small. Ideally, the parliamentary threshold, which was previously 4% in the 2019 election, is raised to 8% in the 2024 election. Thus, a strong, effective and stable presidential government system with only 4 (four) to 6 (six) political parties will be realized.